The first observation of the hot ion mode at the Globus-M2 spherical tokamak. (1st October 2022) - Kurskiev, G.S.; Miroshnikov, I.V.; Sakharov, N.V.; Gusev, V.K.; Petrov, Yu.V.; Minaev, V.B.; Balachenkov, I.M.; Bakharev, N.N.; Chernyshev, F.V.; Goryainov, V.Yu.; Kavin, A.A.; Khromov, N.A.; et al.
Abstract: Hot ion mode was recently achieved at the Globus-M2 spherical tokamak when the toroidal magnetic field was as high as 0.9 T and plasma current 0.35 MA. The injection of two neutral beams with a total power of 0.7 MW and an energy of 30 keV into a plasma with major radius 0.36 m and minor radius 0.22 m (aspect ratio 1.6) made it possible to heat the plasma ions up to 4 keV, while electron density in the plasma center was as high as 8 × 10 19 m −3 . The achievement of high temperatures became possible due to the good thermal insulation of the plasma.